MEANING AND FORM IN NURSERY RHYMES TRANSLATION - Ikke Dewi Pratama (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2017)
MAKNA DAN BENTUK DALAM PENERJEMAHAN LAGU-LAGU ANAK AbstractTranslating nursery rhymes is not an easy task. The problems of equivalence in meaning and form as well as in the harmony between the translated lyrics and the music are aspects that need to be considered by the translators. By considering nursery rhyme lyric as poetry text, this research analyzes the equivalence of meaning and form in nursery rhymes translation. This research focuses on five nursery rhymes. The meaning analysis was done by conducting particular procedures on translation quality assessment. Meanwhile, the analysis of the form was conducted by comparing the two versions of the nursery rhymes focusing on the sound values. From the equivalence of meaning, the result shows that most nursery rhymes are translated less accurately. On the other hand, the finding of the equivalence in form shows that most of the auditory devices are deleted while most of the rhymes are shifted. This research is expected to give a contribution to song translation activities especially those involving children as the target listeners. Keywords: equivalence, accuracy, sound values, auditory devices, rhymes AbstrakMenerjemahkan lagu anak bukanlah hal yang mudah. Masalah kesepadanan makna dan bentuk, serta harmonisasi antara lirik terjemahan dan musik adalah aspek-aspek yang harus dipertimbangkan oleh penerjemah. Dengan mempertimbangkan lirik lagu anak sebagai teks puisi, penelitian ini menganalisis kesepadanan antara makna dan bentuk dalam terjemahan lagu anak. Dengan menggunakan teknik sampling, penelitian ini berfokus kepada lima lagu anak. Analisis makna dilakukan dengan prosedur penelitian kualitas terjemahan sedangkan analisis bentuk dilakukan dengan membandingkan dua versi lagu anak dengan fokus kepada sound values (bunyi). Analisis kesepadanan makna menunjukkan bahwa sebagian besar lagu anak diterjemahkan dengan kurang akurat. Dari segi bentuk, sebagian besar auditory devices dihapus sedangkan sebagian besar rima bergeser. Penelitian ini diharapkan dapat memberikan kontribusi terhadap penerjemahan lagu khususnya yang melibatkan anak-anak sebagai pendengar sasaran. Kata kunci: kesepadanan, keakuratan, sound values, auditory devices, rima